1969
DOI: 10.1246/bcsj.42.2312
|View full text |Cite
|
Sign up to set email alerts
|

Cooxidation of Hydrocarbons in Liquid Phase. VI. Reactivities of Hydrocarbons and Peroxy Radicals

Abstract: the peroxy radicals were approximately in the ratio 15 : 10 : 5 : 1. It was also concluded that the secondary peroxy radicals were more reactive than the tertiary peroxy radicals and that the polymeric peroxy radicals were more reactive than the normal alkylperoxy radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…The values of the reactivity ratios reveal, that AMS is nearly four times more reactive towards the peroxide radical than STY. The r values calculated from the Kelen‐Tudos plots are consistent with those reported earlier 22. The calculation of the reactivity ratios from NMR data is rather straightforward.…”
Section: Resultssupporting
confidence: 87%
“…The values of the reactivity ratios reveal, that AMS is nearly four times more reactive towards the peroxide radical than STY. The r values calculated from the Kelen‐Tudos plots are consistent with those reported earlier 22. The calculation of the reactivity ratios from NMR data is rather straightforward.…”
Section: Resultssupporting
confidence: 87%
“…This also indicates that the peroxide radical is more reactive towards monomers having more electron‐donating ability. The reactivity ratio values calculated in this study match well with those reported earlier . However, r AMS = 0.98 and r St = 0.67 are also reported for the AIBN‐initiated copolymerization of AMS with St at 50 °C at 1 atm (101 kPa) oxygen pressure .…”
Section: Resultssupporting
confidence: 90%
“…The chemical shifts are measured with reference to tetramethylsilane (TMS). The 13 C NMR spectra were obtained under inverse gated decoupling with 15 s delay between the pulses. A line broadening of 2 Hz was applied before Fourier transformation in order to enhance the signal-to-noise ratio.…”
Section: Measurementsmentioning
confidence: 99%
“…[2] In an earlier work on the oxidative copolymerization, relative rates of oxidation of different monomers and their reactivity towards a peroxide radical was investigated. [12,13] The oxidation of two monomers can be considered as a special case of terpolymerization, when the monomers do not homopolymerize. The uniqueness of this system is that it approximates to a binary copolymerization in terms of 1RO 2 9 radicals.…”
Section: Introductionmentioning
confidence: 99%